An APOO Pseudogene on Chromosome 5q Is Associated With Low-Density Lipoprotein Cholesterol Levels. Issue 13 (25th September 2018) - Montasser, May E.; O'Hare, Elizabeth A.; Wang, Xiaochun; Howard, Alicia D.; McFarland, Rebecca; Perry, James A.; Ryan, Kathleen A.; Rice, Kenneth; Jaquish, Cashell E.; Shuldiner, Alan R.; Miller, Michael; Mitchell, Braxton D.; et al.
Abstract : Background: Elevated levels of low-density lipoprotein cholesterol (LDL-C) are a major risk factor for cardiovascular disease via its contribution to the development and progression of atherosclerotic lesions. Although the genetic basis of LDL-C has been studied extensively, currently known genetic variants account for only ≈20% of the variation in LDL-C levels. Methods: Through an array-based association analysis in 1102 Amish subjects, we identified a variant strongly associated with LDL-C levels. Using a combination of genetic analyses, zebrafish models, and in vitro experiments, we sought to identify the causal gene driving this association. Results: We identified a founder haplotype associated with a 15 mg/dL increase in LDL-C on chromosome 5. After recombination mapping, the associated region contained 8 candidate genes. Using a zebrafish model to evaluate the relevance of these genes to cholesterol metabolism, we found that expression of the transcribed pseudogene, APOOP1, increased LDL-C and vascular plaque formation. Conclusions: Based on these data, we propose that APOOP1 regulates levels of LDL-C in humans, thus identifying a novel mechanism of lipid homeostasis. Abstract : Supplemental Digital Content is available in the text.